MILLIY IQTISODIYOTDA INVESTITSION JOZIBADORLIKNI OSHIRISH OMILLARI VA STRATEGIYALARI (Marketing Journal, 2026)
AbstractThe study analyzed factors and strategic directions for increasing investmentattractiveness in the national economy. Macroeconomic stability, institutional quality,infrastructure development, human capital level, and innovation potential wereassessed as key components shaping the investment environment. The analysis wasconducted using Dunning’s OLI paradigm and Porter’s competitiveness theory. Datafrom UNCTAD, the World Bank, the IMF, and national statistics were used to examinethe dynamics of investment activity in Uzbekistan. The results showed thatimprovement of the legal environment, acceleration of digital transformation,development of cluster policy, and application of tax incentives significantlyinfluenced the expansion of investment flows. The research formulated scientificconclusions aimed at strengthening the investment potential of the national economy.Keywords: investment attractiveness, OLI paradigm, institutional environment,human capital, digital transformation, cluster policy, national economy, strategicmanagement, FDI.